Production of Horse-Drawn Carriages in Latvia in the 20th Century - Zvirgzdiņš, Indulis (History of Engineering Sciences and Institutions of Higher Education, 2020)
In the first half of the last century, wood craftsmen and blacksmiths collaborated in the manufacture of carriages, but in most cases, they worked individually. There were also larger companies operating mainly in cities. The author’s main focus is on the Madona area. The carriage and sled workshop of Augusts Mazurs (1885–1975), which was the most significant in the area, is used as an example. It was established in 1924 and continued its work during the Soviet era. Horse-drawn carriages were the main mode of local transport in the Republic of Latvia and its territory also in the decade after World War II. Later, the role of road transport gradually increased. Carriages and sleds were made on site, most cars were imported.